FORMATION OF NATIONAL IDENTITY AWARENESS COMPETENCE IN THE EDUCATIONAL PROCESS. - Tilakova Mavjuda,Shadikulova Mukarram Tagaymuratovna (International Journal of Literature and Language Studies, 2026)
This article highlights the theoretical and methodological foundations, pedagogical mechanisms, and practical significance of developing the competence of national identity awareness in the educational process. National identity awareness is analyzed as an important indicator of an individual's spiritual maturity, and the ways of developing this competence through the integration of national values into the content of education are substantiated.